Análise de indicadores de desenvolvimento socioemocional, temperamento e comportamento em crianças de risco - Jesus, Thais Costa (2021)
Follow-up Programs monitor, multidisciplinarily and periodically, children with risk factors, aiming to identify and to prevent diseases and negative outcomes related to child development, in order to minimize developmental delays and/or sequelae as soon as possible. In this field, the knowledge created by research on temperament is relevant, since this is a predictor construct of child vulnerability to behavioral problems or, in the extreme, to psychopathological conditions. Based on Rothbart’s approach, temperament is defined as individual constitutional differences in reactivity (in emotion, activity and attention) and in self-regulation; reactivity is the latency, intensity and duration of responsiveness to stimulation, whereas self-regulation is the process that serves to modulate this reactivity. Considering the relevance of this variable, the objective of this study is to analyze, in addition to temperament, behavioral and social-emotional developmental indicators in children enrolled to Follow-up Programs. The sample has been composed of 36 participants 1.5 to 3.5 years old, enrolled to different Programs. Their legal persons have filled out the following instruments: a) Data protocols; b) ABEP’s CCEB-2015, 2019 update; c) Early Childhood Behavior Questionnaire - ECBQ 18–36 month olds and Childhood Behavior Questionnaire - CBQ 3-7 year olds; d) Bayley-III Social-Emotional Scale; and e) Child Behavior Checklist – CBCL/1.5-5 years and f) Strength and Difficulties Questionnaire – SDQ 2-4p. The data have been analyzed using descriptive and inferential statistics. The obtained results shows that approximately 8% of the sample present emotional development as possible challenges; more than 60% of the sample has average scores in all domains of temperament, and 16.2% present total behavior problems, 16.2% internalizing problems and 10.8% externalizing problems. In this study, temperament has not been statistically significant for social-emotional development; however, it has for behavioral problems (mainly Effort Control). It is perceived that Internalizing Problems has been associated with Negative Affectivity and externalizing problems, with Effort Control. There has been no statistical difference between different age groups, but there has been a higher incidence of internalizing and externalizing problems in children older than 2 years. And stress is the highest rate category in both groups. Comparing preterm and term groups, there has been no statistical difference; however, it has been observed that the preterm group has presented a higher score for Extroversion and a lower rate of behavioral problems. There has also been detected an interrelation between higher family income and better Effort Control scores, fewer externalizing problems and fewer total behavior problems. The results facilitate the early developmental problems identification in the sample and they contribute to the discussion on inclusion of instruments for assessing temperament and social-emotional and behavioral profiles as part of the Follow-up Programs routine, especially when it comes to emotional development aspects, improving the service quality by providing other relevant and consistent basis for early intervention strategies analysis in child mental health.